SELF-DIRECTED LEARNING IN EFL DURING COVID-19 PANDEMIC: AN ANALYSIS OF TEACHER’S PERCEPTIONS AND STUDENTS’ LEARNING AUTONOMY IN SMAN 1 SEMARAPURA - Made Surya Adi Putra; Luh Putu Artini; Ni Nyoman Padmadewi (Language and Education Journal Undiksha, 2021)
The purpose of this study is to analyze how the English teacher perception about Self-directed learning, to describe the activities assigned by the teacher in online learning, and to identify Self-directed Learning components that appears in the activities assigned by the teacher. The research design in this study used embedded mix-method research design which the data was dominant presented in a qualitative data and then supported by quantitative data. The subject of this study was one English teacher who teach in tenth grade students in SMA 1 Semarapura in Klungkung Regency. There were four research instruments used in this study, those are researcher, questionnaire, observation table, and identification table. There were three main result of this research. Firstly, the teacher has positive responses for the all of the aspects of perception in questionnaires which knowledgeable in terms of knowledge, very anticipated in terms of implementation and, influential in terms of impact. Secondly, the activities assigned is not optimal yet especially in the post activity and whilst activity. Thirdly, there are two Self-directed Learning components with four indicators appeared in the activities assigned by the teacher. The data showed that there was a mismatch between teacher perception and activities assigned by the teacher in online learning.